Wood biochar produces different rates of root growth and transpiration in two maize hybrids (Zea mays L.) under drought stress. Issue 6 (12th May 2019) - Romdhane, Leila; Awad, Yasser Mahmoud; Radhouane, Leila; Dal Cortivo, Cristian; Barion, Giuseppe; Panozzo, Anna; Vamerali, Teofilo
ABSTRACT: This study investigated the effects of wood-derived biochar (BC) applied at 1% to a C-poor silty-loam soil in the drought-tolerant (D24) and in the drought-sensitive (P1921) Pioneer Hi-Bred maize hybrids in pot and field trials (NE Italy). D24 had better growth than P1921 under rain-fed conditions without irrigation and soil amendment. The addition of biochar increased root growth in D24 (+38% root area) and decreases it in P1921 (−9%) at the silking stage, while the fraction of finer roots (<250 µm diam.) was reduced in D24 and increased in P1921. This led both hybrids to maintain the maximum transpiration at a lower fraction of transpirable soil water (from 82% to 45% in D24, and from 46% to 22% in P1921). There were no significant variations in plant nutrient contents, productivity and in the protein and starch contents of the grains, whereas the lipid content was reduced by biochar, particularly in P1921 (2.6% vs. 3% DW, −13%). We conclude that biochar can be profitably used to enhance drought tolerance in maize, possibly due to improvements in the physicochemical characteristics and the water content of treated soils, although maximum benefits are expected in drought-tolerant hybrids through increased root elongation and transpiration.